Plasma levels of lipometabolism-related miR-122 and miR-370 are increased in patients with hyperlipidemia and associated with coronary artery disease - Gao Wei; He Hui-Wei; Wang Ze-Mu; Zhao Huan; Lian Xiao-Qing; Wang Yong-Sheng; Zhu Jun; Yan Jian-Jun; Zhang Ding-Guo; Yang Zhi-Jian; Wang Lian-Sheng (Lipids in Health and Disease, 2012)
Abstract Background Hyperlipidemia plays a crucial role in the development and progression of coronary artery disease (CAD). Recent studies have identified that microRNAs (miRNAs) are important regulators of lipid metabolism, but little is known about the circulating levels of lipometabolism-related miRNAs and their relationship with the presence of CAD in patients with hyperlipidemia. Methods In the present study, we enrolled a total of 255 hyperlipidemia patients with or without CAD and 100 controls with normal blood lipids. The plasma levels of four known lipometabolism-related miRNAs, miR-122, miR-370, miR-33a, and miR-33b were quantified by real-time quantitative PCR. Blood levels of total cholesterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-C), and high density lipoprotein cholesterol were determined. Furthermore, the severity of CAD was assessed with the Gensini score system based on the degree of luminal narrowing and its geographic importance. Results Our results revealed for the first time that plasma levels of miR-122 and miR-370 were significantly increased in hyperlipidemia patients compared with controls, and the levels of miR-122 and miR-370 were positively correlated with TC, TG, and LDL-C levels in both hyperlipidemia patients and controls. Multiple logistic regression analysis demonstrated that the increased levels of miR-122 and miR-370 were associated with CAD presence, even after adjustment for other cardiovascular risk factors. Furthermore, miR-122 and miR-370 levels were positively correlated with the severity of CAD quantified by the Gensini score. However, both miR-33a and miR-33b were undetectable in plasma. Conclusions Our results suggest that increased plasma levels of miR-122 and miR-370 might be associated with the presence as well as the severity of CAD in hyperlipidemia patients.